Arbitration as a Legal Mechanism in the Settlement of Disputes under Cameroonian Law - Tambe, Hans; Forbi, Nduah Esther; Epie, Mousinga Adele (Social Science Research Network, 2021)
Recently, commercial activities in the state of Cameroon are evolving and there is an inflow of investors from within the OHADA Zone and other regions of the world to Cameroon. This has led to the proliferation of commercial contracts such as concession contracts, production sharing agreements, risk contracts between the Republic of Cameroon and foreign investors, or contracts between individuals of foreign countries as well as with Cameroonian nationals. Commonly, contracts may be breached and disagreements surface among the contracting parties. The difficulties pose is in the manner to settle such disagreements in a friendly manner to maintain the relationship between the parties and to enables the contracting parties to resolve the disputes more cost-effectively and increase business efficiency in Cameroon. However, the state of Cameroon has a favorable attitude towards bilateral and multilateral investment treaties to guarantee protection to investors in the territory. This elucidates the reason why the government of Cameroon has enacted laws and ratified regional and international treaties, aimed at safeguarding a smooth atmosphere for investors and other commercial traders particularly in the domain of arbitration to help in resolving disputes in case of any disagreement among contracting parties. This article will present the authorities involved in arbitration with the experience regarding the application of the various law and institutions concerned with the arbitration. This will also help contracting parties or investors to understand the legal mechanisms in the settlement of disputes through arbitration in Cameroon.
Keywords: Arbitrage; Arbitragem; Arbitration; dispute; legal; mechanism; settlement

60 Years of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1958: Are We There Yet in Sub-Saharan Africa? - Okubote, Abayomi (Social Science Research Network, 2018)
Sub-Saharan Africa has, in recent years, been classified as a natural-resource play for foreign investors. These investment potentials have made the region one of the most attractive investment destinations in the world. The region is also diverse, with a mix of different legal systems and legal traditions. While investors are constantly seeking to understand the different legal regimes, international arbitration offers comfort by providing a framework for the enforcement of rights in a neutral forum and on a different platform. According to the World Bank, the ability to enforce an arbitral award is an important factor for investors considering potential markets in which to invest.Given the sixtieth anniversary celebration of the New York Convention (NY Convention), this article examines the enforcement regimes for arbitral awards in sub-Saharan Africa. It considers the momentous developments in the enforcement regimes in the region, due to the implementation of the NY Convention. It examines the proposed amendments to the enforcement provisions in the Nigerian Arbitration Act (Repeal and Re-enactment) Bill 2017, recently passed by the Nigerian Senate. It also examines the important provisions in the revised Uniform Act on the Law of Arbitration and the revised Rules of Arbitration of the Common Court of Justice and Arbitration – both recently adopted by the OHADA Council of Ministers. It attempts a comparison between the enforcement regimes in the OHADA Member States, the NY Convention Member States, and in countries that do not belong to any of the two regimes.A chart of the legal regimes on enforcement of foreign arbitral awards in sub-Saharan Africa is attached as appendix.
Keywords: ACA; Annulment; Arbitral Awards; CCJA; Commercial Arbitration; Convention; Enforcement; Enforcement of Arbitral Awards; Foreign Awards; ICSID Convention; Judiciary; New York Convention; OHADA; Reciprocity; Reservations; Sub-Saharan Africa; Treaty; UAA; UNICTRAL Model law

The Enforcement of Arbitral Awards in Cameroon - Tumnde, Taylor (Social Science Research Network, 2013)
The increase in international trade creates a growing number of disputes between parties from different countries. Arbitration has become the most preferred mechanism to solve disputes in international trade. If a party does not voluntarily comply with an award, the successful party must apply for recognition and enforcement of the award in order to obtain the remedies. Cameroon is one of the major business markets in West and Central Africa, several companies committed to arbitral procedures are likely to have assets in Cameroon. This means that if a party fails to honour an award, an enforcement procedure may begin within a Cameroonian court. The enforcement procedures in Cameroon are sufficient and do comply with international standards. The most used and important instruments for recognition and enforcement are the United Nations Convention on the Recognition and Enforcement of Foreign Arbitral Awards of 1958 and the Uniform Act on Arbitration 1999 in the OHADA territory, to which Cameroon is a signatory State. According to this Convention and the Uniform Act, an arbitral award may be refused enforcement under certain grounds laid down in them. There are various types of arbitral awards contemplated by the Cameroonoan legislature and will be herein examined to see how they can be enforced in Cameroon. An analysis of the legal situation in Cameroon confirms that there are problems associated with the enforcement of arbitral awards. These problems are not, however, connected with the concept of arbitral awards, but rather with the entire judicial system in Cameroon. Even though an enforcing party can do little to overcome these problems, certain measures can be taken in order to ease the enforcement procedure
Keywords: Arbitrage; Arbitragem; Arbitral Awards; Arbitration; Cameroon; Enforcement; OHADA